2015
DOI: 10.1038/ncomms10026
|View full text |Cite
|
Sign up to set email alerts
|

Linc-YY1 promotes myogenic differentiation and muscle regeneration through an interaction with the transcription factor YY1

Abstract: Little is known how lincRNAs are involved in skeletal myogenesis. Here we describe the discovery of Linc-YY1 from the promoter of the transcription factor (TF) Yin Yang 1 (YY1) gene. We demonstrate that Linc-YY1 is dynamically regulated during myogenesis in vitro and in vivo. Gain or loss of function of Linc-YY1 in C2C12 myoblasts or muscle satellite cells alters myogenic differentiation and in injured muscles has an impact on the course of regeneration. Linc-YY1 interacts with YY1 through its middle domain, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(187 citation statements)
references
References 57 publications
4
181
0
Order By: Relevance
“…There are multiple forms of Yam lncRNAs, Yam-1 and -4 appear to inhibit muscle differentiation, while Yam-2 and -3 appear to promote differentiation (13,14). Additionally, linc-YY1 also has been shown to promote differentiation (15). …”
Section: Lncrnas In Myogenesis (Table 1)mentioning
confidence: 99%
“…There are multiple forms of Yam lncRNAs, Yam-1 and -4 appear to inhibit muscle differentiation, while Yam-2 and -3 appear to promote differentiation (13,14). Additionally, linc-YY1 also has been shown to promote differentiation (15). …”
Section: Lncrnas In Myogenesis (Table 1)mentioning
confidence: 99%
“…In contrast to stable mRNAs, most PROMPTs and eRNAs are depleted for 5' splice sites [5] and enriched for polyadenylation sites [6], features which target them for early transcriptional termination and degradation. While the majority of PROMPTs are rapidly degraded, some stable noncoding transcripts produced from promoter regions have been shown to be functional [20, 21]. Some promoter transcripts are reproducibly observed in specific tissues, cell lineages, and cancers, while others are ubiquitous [22].…”
Section: Promptsmentioning
confidence: 99%
“…In a different form of RNA based regulation, YY1 has also been shown to interact with a long intergenic noncoding RNA (lncRNA) transcribed from its own promoter region. When Linc-YY1 binds to YY1 it can de-repress YY1 target genes by causing the eviction of YY1 and PRC2 from gene promoters [20]. Two other well characterized lncRNAs that have been shown to bind PRC2 include COLDAIR in Arabidopsis which mediates repression of the flowering control gene FLC [76, 77] and HOTAIR in Drosophila which regulates the HOXD locus [78].…”
Section: Functions Of Ncrnasmentioning
confidence: 99%
“…13), lnc-YY1 (ref. 20) and lncRNA-Dum21 are also believed as important positively regulators of myogenesis. In contrast, recent studies have shown that certain lncRNAs negatively regulate myogenesis.…”
mentioning
confidence: 99%